Role of calpain system in meat tenderness: A review - Z.F. Bhat; James D. Morton; Susan L. Mason; Alaa El-Din A. Bekhit (Food Science and Human Wellness, 2018)
Aging is a popular method used by meat industry for improving the sensory attributes of meat. Despite the advent of many novel technologies, aging has not lost its charm and is still widely used commercially as a post-mortem intervention for tenderization. Aging improves the tenderness of meat through disruption of the muscle structure by intracellular proteolytic systems. Muscles undergo various molecular changes that cause proteolysis of key myofibrillar and cytoskeletal proteins, disrupting the overall integrity of muscle cells. Although several endogenous proteolytic systems are capable of post-mortem proteolysis, a great body of scientific evidence supports a major role for the calpain system. Calpains are intracellular calcium-dependent cysteine proteases found in most eukaryotes. At least three calpains (μ- and m-calpains and calpain 3) and calpastatin, their specific endogenous inhibitor, are found in muscle. They are known to be involved in the proteolysis of functionally relevant structural proteins such as the myofibrillar proteins and cytoskeletal anchorage complexes. These ubiquitous proteases are also present in mitochondria and play important roles in a variety of pathophysiological conditions including apoptotic and necrotic cell death phenomena. This review discusses the role and contribution of the calpain system and the factors that influence calpain activity during aging. Keywords: Aging, Tenderness, Calpains, Proteolysis, Calpain activity, Factors